Pengembangan Peran Masyarakat dalam Pengelolaan Lingkungan Terpadu di Desa Libo Jaya, Kandis - Fitmawati, Fitmawati; Elvyra, Roza; Anisa, Nur; Sinaga, Adinda Patricia Adelina; Hakim, Zalika Auliasari; Agustin, Hawa Merdika; Fajrin, Joane; Nurfadhila, Amanda (Penerbit Goodwood, 2024)
Purpose: The service carried out aims to increase the role of the community in Libo Jaya Village, Kandis District, Riau Province in managing an integrated and economically valuable environment. This is motivated by the growth of the agricultural and plantation sectors in Indonesia, especially in Riau Province, which is driven by the wealth of natural resources, especially through oil palm planting Methodology: This community service uses a combination of quantitative and qualitative approaches. Data was collected through surveys, interviews and participant observation to evaluate the program's impact on increasing community awareness and their involvement in environmental management efforts. Results: The results of the activities show that the ecoprint and ecoenzym Training Program has succeeded in increasing the role of society in environmental management. Through the application of environmentally friendly technologies such as ecoprint and ecoenzym, the people of Libo Jaya Village not only get economic benefits, but also become agents of change in preserving their environment. Conclusions: This activity has successfully enhanced the knowledge and skills of the local community. In line with community expectations, the level of public understanding of ecoprint and ecoenzyme has increased significantly by up to 55%. The achievements gained through this initiative mark a strong starting point for integrated and economical environmental management in a sustainable manner. Limitation: The number of participants in the service program was limited. This activity involved various elements of local society, especially housewives in Libo Jaya Village, Kandis District, Siak with a total participation of around 30 people. Contribution: This program also encourages collaboration between communities, local governments and the private sector in creating sustainable solutions to environmental problems.